The Influence of The Physical Work Environment and Organizational Climate on Employee Performance Through Job Satisfaction as an Intervening Variable in PT. Bank Tabungan Negara (Persero) Tbk South Tangerang Branch - Bekti Dwi Widiastuti (Return : Study of Management, Economic and Bussines, 2024)
This study was conducted to determine the influence of the physical work environment and organizational climate on employee performance through job satisfaction as an intervening variable in PT. Bank Tabungan Negara (Persero) tbk South Tangerang branch office. This research method uses quantitative methods using survey techniques. The population used in this study were staff employees at PT. Bank Tabungan Negara (Persero) tbk South Tangerang branch office.  The sampling technique uses random sampling, the number of sampling used in this study was 118 respondents. Data collection for each variable studied using questionnaires with Likert scale and rating scale. Data analysis techniques use descriptive statistical analysis techniques and PLS (Partial Least Square) analysis techniques. The results of this study show that there is a positive and significant influence of the physical work environment on performance, there is a positive and significant influence of the physical work environment on job satisfaction, there is a positive and significant influence of organizational climate on performance, there is a positive and significant influence of organizational climate on job satisfaction, there is no effect of job satisfaction on performance, there is no positive and significant influence of the physical work environment On performance through job satisfaction, there is no positive and significant influence of organizational climate on performance through job satisfaction.